2005
DOI: 10.1063/1.2115078
|View full text |Cite
|
Sign up to set email alerts
|

Germanium n+∕p junction formation by laser thermal process

Abstract: In this letter, an n+∕p junction on a germanium substrate, formed by phosphorous implantation and subsequent laser thermal annealing process, is demonstrated. The effects of laser energy fluence and irradiation pulse number on the redistribution of dopant atoms have been investigated. The secondary-ion-mass-spectrometry results indicate that steplike dopant profiles are formed with dopant atoms extending deeper upon increased laser energy fluence and successive pulse number. After being irradiated at a laser e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…This is, e.g., demonstrated by laser thermal processing of P-implanted Ge for the formation of nþ/p junctions. 7,80,90 Laser annealing above the melting threshold followed by SPER eliminates implantation damage and reduces donor diffusion to the Ge surface and bulk, which would limit the maximum doping level. On the other hand, RTA treatments at low processing temperatures are also sufficient to remove implantation damage and to suppress donor diffusion as demonstrated by Satta et al 63 and Chui et al, 91 but the low processing temperatures required to limit donor diffusion will favor the formation of dopant-defect complexes and thus donor deactivation.…”
mentioning
confidence: 99%
“…This is, e.g., demonstrated by laser thermal processing of P-implanted Ge for the formation of nþ/p junctions. 7,80,90 Laser annealing above the melting threshold followed by SPER eliminates implantation damage and reduces donor diffusion to the Ge surface and bulk, which would limit the maximum doping level. On the other hand, RTA treatments at low processing temperatures are also sufficient to remove implantation damage and to suppress donor diffusion as demonstrated by Satta et al 63 and Chui et al, 91 but the low processing temperatures required to limit donor diffusion will favor the formation of dopant-defect complexes and thus donor deactivation.…”
mentioning
confidence: 99%
“…GILD experiments on Ge are motivated by recent publications reporting that LTP is able to overcome limitations encountered on P-doping of Ge since shallow junctions with active P concentrations of about 10 20 cm − 3 can be obtained [6][7][8]. Results on GILD of SiGe have been published previously [10][11], but, to our knowledge, GILD results on pure germanium have not been published already.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 90%
“…Furthermore, the introduction of germanium and IV-IV alloys in the CMOS technology, for microelectronics or optoelectronics, reveals that germanium doping is facing specific difficulties, such as fast dopant diffusion induced by thermal annealing (specially in the case of phosphorus), and low active dopant concentrations due to dopant solid-solubility limitation [1][2][3]. In this context, laser doping techniques appear as attractive solutions to realize thermal annealing after dopant implantation (laser thermal processing (LTP) or annealing (LTA) [4][5][6][7][8]), or as an in situ doping process (gas immersion laser doping (GILD) [9][10][11][12][13]). Most of the LTP and GILD published results concern silicon, while only few publications deal with LTP experiments on germanium [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that dopant activation and contact resistance can be dramatically improved by LTA in the melt regime [72,[93][94][95][96][97][98]. Control of melt-depth is done by changing laser energy density.…”
Section: Access Resistance 51 Doping Optimisationmentioning
confidence: 99%